Role of Central Metal Ions in 8‐Hydroxyquinoline‐Doped ZnO Interfacial Layers for Improving the Performance of Polymer Solar Cells. Issue 22 (30th September 2018) - Babu, B. Hari; Lyu, Chengkun; Yu, Chengzhuo; Wen, Zhenchuan; Li, Fenghong; Hao, Xiao‐Tao
Abstract: Optimizing the function of interfacial materials between the photoactive layer and the metal cathode is critical for realizing high‐efficiency organic solar cells (OSCs). The charge‐collecting layer requires a material with an excellent electrical property to improve the charge collection efficiency and decrease the leakage current that increases the power conversion efficiency (PCE). In this study, the performance of sol–gel‐derived modified cathode interfacial (ZnO) layers, prepared by an appropriate doping of metal (M = Al, Ga, and Mn)quinoline (Q) groups in OSCs, is demonstrated and evaluated. The light absorption of the photoactive layer is improved upon incorporating an interfacial layer into the OSCs. The PCE of the GaQ:ZnO‐based device is higher than that of the AlQ:ZnO and MnQ:ZnO‐based devices, attributed to an improved exciton dissociation rate, enhanced carrier transport, greater electron mobility, and a lower work function. Incorporating a GaQ:ZnO interfacial layer into a thieno[3, 4‐ b ]thiophene/benzodithiophene:[6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PTB7:PC71 BM) OSC increases the PCE from 7.51% to 8.44%, and incorporating it into a poly[[2, 6′‐4‐8‐di(5‐ethylhexylthienyl)benzo[1, 2‐ b :3, 3‐ b ]dithiophene][3‐fluoro‐2[(2‐ethylhexyl) carbonyl]thieno[3, 4‐ b ]thiophenediyl:[6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PTB7‐Th:PC71 BM) (PTB7‐Th:PC71 BM) OSC increases the PCE from 8.11% to 9.02%. Abstract : The performance of ZnO interfacial layers doped with metal–quinoline (Q) groups is demonstrated in organic solar cells (OSCs). The light absorption of the photoactive layer is improved upon incorporating a doped interfacial layer into OSCs. The power conversion efficiency of OSC with GaQ:ZnO interfacial layer can be substantially increased attributed to an improved exciton dissociation rate, enhanced carrier transport, and a lower work function.